Intravenous single dose of tranexamic acid safely reduces blood loss and the need for transfusion in elderly patients with hip fracture. A randomized double-blinded controlled trial at 1-year follow-up - Francisco A Miralles-Muñoz; Rosario Martin-Grandes; Daniel Martinez-Mendez; Gerard Mahiques-Segura; Alejandro Lizaur-Utrilla; María Flores Vizcaya-Moreno (Annals of Musculoskeletal Medicine - Peertechz Publications, 2023)
Background: A hip fracture usually presents significant blood loss in the perioperative period, with a transfusion rate of 20-60%. In order to reduce the complications associated with this procedure, the administration of Tranexamic Acid (TXA) has been implemented in the treatment of perioperative anemia. The objectives were to evaluate the effectiveness and safety of a single dose of intravenous Tranexamic Acid (TXA) in reducing perioperative blood loss and the requirement for transfusion in elderly patients undergoing hip fracture surgery within one postoperative year. Methods: A double-blind randomized controlled trial was conducted on 129 patients with hip fractures. After randomization, at the start of the surgery, 65 patients received a single dose of 1 gram of intravenous TXA (TXA group), and 64 received a placebo (placebo group). The primary effectiveness outcomes were the total blood loss and transfusion rate. The primary safety outcome was the rate of thromboembolic events. Data on surgical or medical infection, readmission and death were also collected. Results: The TXA group had a significant decrease in blood loss (p = 0.006) and requirement for transfusion (p < 0.001) compared with the placebo group. Likewise, there were no thromboembolic events in the TXA group and seven in the placebo group (p = 0.006). Mortality within 1-year postoperatively was not significantly different (p = 0.115). Conclusion: Using a single dose of intravenous TXA at the start of the surgery significantly reduces blood loss and the requirement for transfusion without increasing the risk of thromboembolic events or mortality within 1-year postoperatively in patients with hip fracture undergoing surgery. Registration number: NCT03211286. https://clinicaltrials.gov/ct2/show/NCT03211286. Level of evidence: I.